Upaya Guru PAI dalam Penanaman Ibadah Peserta Didik di SMA Muhammadiyah 3 Jakarta - Hamidah Salsabila; Heru Wibowo (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
In Madrasas, the values ​​of worship are used to advance the teaching of the Islamic religion. Apart from madrasas, a number of public schools also implement religious teaching. The development of religious worship is an effort to uphold the principles of the Islamic religion while producing quality human beings who are able to compete in the modern global world. The aim of this research is to find out the principles of worship adhered to by SMA Muhammadiyah 3 Jakarta as well as the strategies used by PAI teachers. The method used in this research is descriptive qualitative. Primary data was taken through observation, interviews and documentation methods from teachers at SMA Muhammadiyah 3 Jakarta. The results of this research found that the values ​​of worship instilled in SMA Muhammadiyah 3 Jakarta are the value of piety, the value of discipline, the value of patience and the value of honesty. The strategy used by PAI teachers in instilling the value of worship at SMA Muhammadiyah 3 Jakarta is through the activities of Maghrib and Isha prayer imams scheduled in class (for boys only), morning coaching, menstruation coaching, midday prayer coaching on Fridays for female students, and mabit activities for students who are subject to sanctions because they do not meet the criteria determined by the tahfidz teacher. All the values ​​of worship have been implemented well, but students still need to be reminded and given motivation to be enthusiastic about implementing them. this research found that the values ​​of worship instilled in SMA Muhammadiyah 3 Jakarta are the value of piety, the value of discipline, the value of patience and the value of honesty. The strategy used by PAI teachers in instilling the value of worship at SMA Muhammadiyah 3 Jakarta is through the activities of Maghrib and Isha prayer imams scheduled in class (for boys only), morning coaching, menstruation coaching, midday prayer coaching on Fridays for female students, and mabit activities for students who are subject to sanctions because they do not meet the criteria determined by the tahfidz teacher. All the values ​​of worship have been implemented well, but students still need to be reminded and given motivation to be enthusiastic about implementing them.